2010
DOI: 10.1007/s00395-010-0143-y
|View full text |Cite
|
Sign up to set email alerts
|

Ischemia/reperfusion injury is increased and cardioprotection by a postconditioning protocol is lost as cardiac hypertrophy develops in nandrolone treated rats

Abstract: We hypothesized that Nandrolone (ND)-abuse induces cardiac hypertrophy, increases myocardial susceptibility to ischemia/reperfusion (I/R) injury, and reduces responsiveness to postconditioning (PostC) cardioprotection. Wistar-rats were ND-treated for 2-weeks (short_ND) or 10-weeks (long_ND). Vehicle-treated rats served as controls. Hearts were retrogradely perfused and left ventricular pressure (LVP) was measured before and after 30-min global ischemia. In subgroups of hearts, to induce cardioprotection a Post… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
31
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 60 publications
5
31
0
1
Order By: Relevance
“…However, this increase was completely absent in hypertensive, hypertrophied rat hearts . In anabolic steroid-induced cardiac hypertrophy, ischemic postconditioning failed to reduce infarct size after ischemia/reperfusion; postconditioning increased Akt phosphorylation regardless of its protective effects, but reduced expression of protein phosphatase expression was measured in protected hearts (Penna et al, 2011). Chronic captopril treatment significantly reduced left ventricular hypertrophy in hypertensive rats and reduced infarct size after ischemia/reperfusion in isolated hearts from both normotensive and hypertensive rats.…”
Section: B Hypertension Cardiac Hypertrophy and Remodelingmentioning
confidence: 90%
“…However, this increase was completely absent in hypertensive, hypertrophied rat hearts . In anabolic steroid-induced cardiac hypertrophy, ischemic postconditioning failed to reduce infarct size after ischemia/reperfusion; postconditioning increased Akt phosphorylation regardless of its protective effects, but reduced expression of protein phosphatase expression was measured in protected hearts (Penna et al, 2011). Chronic captopril treatment significantly reduced left ventricular hypertrophy in hypertensive rats and reduced infarct size after ischemia/reperfusion in isolated hearts from both normotensive and hypertensive rats.…”
Section: B Hypertension Cardiac Hypertrophy and Remodelingmentioning
confidence: 90%
“…Accordingly, the preconditioning effect of prodromal angina is reportedly attenuated in acute myocardial infarction patients with hypertensive LVH (203). It also seems to be the case with cardioprotection by ischemic (150) and pharmacological (151) postconditioning, although few studies have been published on this point.…”
Section: Comorbidities and Cardioprotection: Prevailing Knowledge Intmentioning
confidence: 99%
“…Notwithstanding in increasing the susceptibility to myocardial infarction and stroke by the above-mentioned abnormalities, chronic administration of AS has been shown to increase the damage induced by myocardial ischemia and reperfusion, which per se can aggravate the post-infarction prognosis [59][60][61]. Furthermore, recent evidences have demonstrated that therapeutic efficacy of cardioprotective maneuvers against the myocardial ischemia/reperfusion injury can be abolished by chronic exposure to AS [62]. Biochemical and molecular analyses revealed that supraphysiological doses of AS are related to redox imbalance, increased proinflammatory signaling, and overactivation of renin-angiotensin system in the heart, which seems to be closely correlated to the loss of cardioprotection after myocardial ischemia/reperfusion injury [55,60,61,63].…”
Section: Cardiovascular Effectsmentioning
confidence: 99%